Animated Activity Questionnaire (AAQ), a new method of self‐reporting activity limitations in patients with hip and knee osteoarthritis: Comparisons with observation by spouses for construct validity. (7th December 2016) - Peter, W.F.; Dagfinrud, H.S.; Østerås, N.; Terwee, C.B.
Abstract: Objective: The aim of the present study was to evaluate the construct validity of the Animated Activity Questionnaire (AAQ) for measuring activity limitations of patients with hip and knee osteoarthritis (HKOA). Design: In a psychometric design, data from HKOA patients and their spouses in Norway and the Netherlands were collected independently of each other, using the AAQ, the Function of Daily Living (FDL) subscale from the Hip disability or Knee injury Osteoarthritis Outcome Scale (H/KOOS) and the Numerical Rating Scale for pain (NRS‐pain). By showing standardized animations on a computer, the AAQ minimizes the influence of the patient's own frame of reference. Therefore, we expected a strong correlation (≥ 0.6) for the AAQ, between patients and spouses. By contrast, we expected a moderate correlation (0.3–0.6) between patients and spouses on the H/KOOS and the NRS‐pain. Analyses were carried out by partial correlations. Results: In total, 29 Norwegian and 30 Dutch patients with HKOA and their spouses participated. A high correlation between patient and spouse scores on the AAQ ( r  = 0.61) was confirmed, but the correlations between patient and spouses scores on the H/KOOS FDL subscale (0.55) and NRS‐pain (0.64) were higher than expected, indicating that spouses may have insight not only into the observed activity limitations of the patient (as measured by the AAQ), but also into patients' subjectively perceived activity limitations (as measured by written questionnaires). Conclusions: The construct validity of the AAQ was supported by a high correlation between patients' and spouses' scores. Our hypothesis that spouses are less influenced by patients' subjective frame of reference in responding to self‐report questionnaires may not be correct.